Skip to content

Instantly share code, notes, and snippets.

@vermiculus
Created April 3, 2014 01:05
Show Gist options
  • Star 0 You must be signed in to star a gist
  • Fork 0 You must be signed in to fork a gist
  • Save vermiculus/9946499 to your computer and use it in GitHub Desktop.
Save vermiculus/9946499 to your computer and use it in GitHub Desktop.
\documentclass{article}
\usepackage{amsmath}
\begin{document}
\begin{enumerate}
\item \dots
\item \dots
\item \dots
\item \dots
\item \dots
\item \dots
\item \dots
\item Now calculate the logarithm of the $n$th term in the sequence, i.e. $\log a_n$.
Use the series representation of the logarithm to simplify this answer:
\[ \log (1 + x) = -\sum_{k=1}^\infty \frac{(-1)^k}{k} x^k. \]
What do you conclude?
\newcommand\frexp[1]{\frac{(-1)^{#1}}{#1} \cdot \frac{#1}{n^{#1}}}
\begin{align*}
\log (1 + \frac{1}{n})^n
&= - n \cdot \log (1 + \frac{1}{n}) \\
&= - n \cdot (-\sum_{k=1}^\infty \frac{(-1)^k}{k} (\frac{1}{n})^k) \\
&= - n \cdot (\sum_{k=1}^\infty \frac{(-1)^k}{k} (\frac{1}{n})^k) \\
&= - n \left[ \underbrace{\frexp{1}}_{n=1} + \underbrace{\frexp{2}}_{n=2} + \cdots \right] \\
&= \dots
\end{align*}
\end{enumerate}
\end{document}
Sign up for free to join this conversation on GitHub. Already have an account? Sign in to comment